2015
DOI: 10.1371/journal.pone.0134251
|View full text |Cite
|
Sign up to set email alerts
|

Levers for Language Growth: Characteristics and Predictors of Language Trajectories between 4 and 7 Years

Abstract: BackgroundEvidence is required as to when and where to focus resources to achieve the greatest gains for children’s language development. Key to these decisions is the understanding of individual differences in children’s language trajectories and the predictors of those differences. To determine optimal timing we must understand if and when children’s relative language abilities become fixed. To determine where to focus effort we must identify mutable factors, that is those with the potential to be changed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 34 publications
7
100
0
3
Order By: Relevance
“…Several significant direct effects emerged that were in line with the premises of the mediation model and corroborated our hypotheses. Regarding the environmental factors, our data showed that SES and HLE are directly associated with language, replicating previous findings (Farah et al, 2006;Hackman & Farah, 2009;Hart & Risley, 1992;Hoff & Tian, 2005;McKean et al, 2015;Noble et al, 2007;Roberts et al, 2005;Sénéchal & LeFevre, 2014;Wood, 2002). Moreover, consistently with the literature across kindergartners, first graders, and preadolescents (Evans & Schamberg, 2009;Farah et al, 2006;Hackman et al, 2014;Sarsour et al, 2011;Waber et al, 2007), disadvantaged SES was related to impaired temporary memory.…”
Section: The Role Of Ses and Hlesupporting
confidence: 91%
“…Several significant direct effects emerged that were in line with the premises of the mediation model and corroborated our hypotheses. Regarding the environmental factors, our data showed that SES and HLE are directly associated with language, replicating previous findings (Farah et al, 2006;Hackman & Farah, 2009;Hart & Risley, 1992;Hoff & Tian, 2005;McKean et al, 2015;Noble et al, 2007;Roberts et al, 2005;Sénéchal & LeFevre, 2014;Wood, 2002). Moreover, consistently with the literature across kindergartners, first graders, and preadolescents (Evans & Schamberg, 2009;Farah et al, 2006;Hackman et al, 2014;Sarsour et al, 2011;Waber et al, 2007), disadvantaged SES was related to impaired temporary memory.…”
Section: The Role Of Ses and Hlesupporting
confidence: 91%
“…Furthermore, we used reference norms for comparison and did not require studies to include typically developing children. It is known that some variability in scores over time is not unique to ASD (Conti-Ramsden, St Clair, Pickles, & Durkin, 2012;McKean et al, 2015;Ukoumunne et al, 2012) so ideally studies would include other groups of children so language development in ASD can be placed within a developmental context.…”
Section: Considerations For Interpreting Data In This Reviewmentioning
confidence: 99%
“…However, it is unclear whether acceleration describes language trajectories only among the very young, or whether this pattern lasts into adolescence or even adulthood. To the latter point, others have asserted that linguistic growth will naturally plateau when children's skills achieve maturation, suggesting that linguistic trajectories will eventually decelerate to a point of plateau (McKean et al, 2015). To date, understanding of the shape of grammar and vocabulary trajectories is largely piecemeal, given a lack of longitudinal research that transcends the early childhood period and includes measures of both vocabulary and grammar development.…”
Section: Modeling the Nature Of Grammar And Vocabulary Trajectories Frommentioning
confidence: 99%